Are brackish water copepods susceptible to neonicotinoid pesticides? An experimental assessment across different salinity levels - Hiromichi Suzuki; Yasushi Miyamoto; Shinji Takahashi; Jotaro Urabe (Ecotoxicology and Environmental Safety)
Zooplankton are key organisms in aquatic food webs, but due to spatiotemporal salinity fluctuations, estuarine and brackish lakes support only a limited number of zooplankton species. The susceptibility of zooplankton to pesticide contamination, such as imidacloprid, is particularly important in these ecosystems, because there are fewer species to compensate for losses. However, whether zooplankton in brackish water are truly vulnerable to pesticide contamination is poorly examined. To address this uncertainty, we assessed the vulnerability of the calanoid copepod Sinocalanus tenellus, a dominant zooplankton in the brackish waters of East Asia, to imidacloprid under varying salinity conditions through individual and population-level experiments. The individual-level experiment revealed that both imidacloprid exposure and salinity changes had significant negative effects on the survival rate of S. tenellus. However, hazard assessments indicated that the risk posed by salinity changes was much greater than that posed by imidacloprid when pesticide concentrations were within ranges typically observed in natural habitats. In the population experiment, imidacloprid exposure had no significant effects on any ontogenetic stages, whereas even small salinity changes significantly affected juveniles of this species. These findings suggest that imidacloprid exposure has a much smaller impact on S. tenellus than salinity changes, except when imidacloprid contamination levels are higher than those typically found in nature. To accurately assess pesticide toxicity in brackish water ecosystems, environmental factors such as salinity must be considered as potential background influences.